2017
DOI: 10.1016/j.conbuildmat.2017.03.130
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of effects of Portland cement fineness and alkali content on concrete plastic shrinkage cracking

Abstract: From a material viewpoint, modern concrete's frequent propensity to plastic shrinkage cracking can be attributable to a combination of low water-binder ratio use and ever-changing properties of binding materials. To obtain a better understanding of this phenomenon, this paper explores the effects of cement fineness and alkali content on the plastic shrinkage cracking of concrete manufactured with two water-binder ratios. Results indicate that within the range 275-385m 2 /kg, cement specific surface area is app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Furthermore, it has been observed that a normal hardening cement boosts the cracking tendency of SCC in comparison to a rapid hardening cement [4]. Finer cement particles, on the other hand, increase the cracking severity [12,13], most probably due to autogenous shrinkage. However, coarser cements cause wider cracks, despite of lower cracking intensity [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been observed that a normal hardening cement boosts the cracking tendency of SCC in comparison to a rapid hardening cement [4]. Finer cement particles, on the other hand, increase the cracking severity [12,13], most probably due to autogenous shrinkage. However, coarser cements cause wider cracks, despite of lower cracking intensity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Finer cement particles, on the other hand, increase the cracking severity [12,13], most probably due to autogenous shrinkage. However, coarser cements cause wider cracks, despite of lower cracking intensity [13]. Another study shows that superplasticizers (SP) increase the evaporation, delay the hydration, and lead to higher cracking risk [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus Building concretes showed lower shrinkage rate than civil engineering concretes in spite of higher drying flux for building concretes. Kai et al [30] found that an increase in cement surface area resulted in lower evaporation rate but higher plastic shrinkage. Slowik et al [29] also showed that early age cracking risk increases with decreasing particle sizes.…”
Section: -Cenmentioning
confidence: 99%
“…Plastic shrinkage depends on water-to-binder (W/B) ratio and cement fineness [29]. An increase in cement fineness and a decrease in W/B ratio led to a decrease in the bleeding rate and an increase the capillary tension level [30]. Plastic shrinkage strain is reduced when the evaporated water is replaced by bleeding water, which could be provided by saturated recycled concrete aggregates [31].…”
Section: Introductionmentioning
confidence: 99%
“…After 300 times of freezing-thawing cycles, the mass loss of RPC with 40% SP is 0.32% and the relative dynamic modulus is 99.3%. Based on the reports about the shrinkage [6][7], freezing-thawing cycles [8][9], and permeability of chloride ions [10][11] for ordinary concrete and RPC, when the SF is replaced by 40% SP, the compactness of the mortar or concrete will be improved with "Filling effect" of SP, which is due to a small particle size that is smaller than cement particle size and bigger than SF particle size. Generally speaking, more compact or less water means less porosity and penetration channel for ions or solution, which finally leads to a better volume stability, a lower mass loss and a higher relative dynamic modulus under freezing-thawing cycles, and a lower electric flux under the penetration of chlorid ions (Table 4).…”
Section: Introductionmentioning
confidence: 99%